EFFECTIVENESS OF DIGITAL STRATEGIC BRANDING FOR MSMEs USING TIKTOK - Diana Novita; Nafisah Yuliani; Nixon Erzed; Agus Herwanto (International Journal of Social Science, 2022)
Brands play an important role in corporate identity and internal image formation people's minds. What's more, we are currently living in the digital age. The emergence of technology boosts MSME activities Enterprise (MSME), including brand building. But the problem is the lack of awareness MSMEs are building a brand, and only a few MSMEs in Indonesia are using digital media. Therefore, it is hoped that small and medium enterprises can increase brand awareness and be able to Accommodating the maximum use of internet media, enabling MSME brands to international market. From the existing problems, it is necessary to discuss the basic concept Small, medium and micro brands, barriers to implementation of small, medium and micro brands, the main key to construction Branding in the digital era, and strategies for building MSME brands. This study uses Qualitative descriptive method, literature study through related books, Journal and Website. The survey results show that the brand strategy is very Implementation is important for the progress and existence of MSMEs Internet media can promote to implement brand strategies.